Degradation of 4-nonylphenol in bromide-containing water by UVC/O3/TiO2-combination processes: Impacts on trihalomethanes and haloacetic acids formation - Muammar Qadafi; Raden Tina Rosmalina; Hanny Meirinawati; Widyarani; Diana Rahayuning Wulan (Emerging Contaminants, 2025)
The presence of nonylphenol (NP) in bromide-containing water contributed to the formation of regulated disinfection by products (DBPs): trihalomethanes-4 (THM4) and haloacetic acids-5 (HAA5). This study was conducted to determine the impact of ozonation initial pH and UVC-combination process in NP, its precursor properties to THM4 and HAA5, degradation. The UVC-combination process was conducted with standalone UVC, UVC/O3, and photocatalytic ozonation using UVC/O3/TiO2. All the process was conducted for 5, 10, 15, 20, 25, and 30min. The samples that have gone through the UVC-combination process were then chlorinated for 24 h to determine the formation of DBPs. The standalone UVC process was sufficient to degrade NP in water with a removal efficiency of 78.99 %. In addition, the UVC/O3 and UVC/O3/TiO2 process enhances significantly the NP degradation, achieving 91.15 % and 99.15 % respectively. Although the NP was successfully degraded during the UVC-combination process, the formation of THM4 and HAA5 increased significantly. The UVC/O3 process is the best choice in removing the NP and THM4 and HAA5 formation with 84.34 %, 94.27 %, and 62.19 % respectively after 5min irradiation process.